LEGAL PROTECTION OF CHILDREN AS VICTIMS OF SEXUAL CRIMES COMMITTED BY PERSONS WITH DISABILITIES - Earlyn Rinani (Yayasan Pendidikan Islam Almatani, 2024)
Children as the younger generation are the greatest wealth for the family, society and nation. They are components that have a big responsibility in determining whether the country will experience progress or decline. Article 28 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that